2017
DOI: 10.1016/j.ab.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of glycation adducts on osteocalcin

Abstract: Osteocalcin is an important extracellular matrix bone protein that contributes to the structural properties of bone through its interactions with hydroxyapatite mineral and with collagen I. This role may be affected by glycation, a labile modification the levels of which has been shown to correlate with bone fragility. Glycation starts with the spontaneous addition of a sugar onto a free amine group on a protein, forming an Amadori product, and then proceeds through several environment-dependent stages resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…5 ). The interaction between OC and other proteins, particularly during glucose metabolism, has been studied ( Garbossa and Folli, 2017 ; Kanazawa, 2015 , 2017 ; Levinger et al., 2017 ; Liu et al., 2015 ; Takeno et al., 2018 ; Thomas et al., 2017 ), whereas the interaction between OC and FBXW2 has not been previously studied. To the author's knowledge, this is the first study to reveal an interaction between OC and FBXW2.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). The interaction between OC and other proteins, particularly during glucose metabolism, has been studied ( Garbossa and Folli, 2017 ; Kanazawa, 2015 , 2017 ; Levinger et al., 2017 ; Liu et al., 2015 ; Takeno et al., 2018 ; Thomas et al., 2017 ), whereas the interaction between OC and FBXW2 has not been previously studied. To the author's knowledge, this is the first study to reveal an interaction between OC and FBXW2.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited evidence of OC glycation in the literature 31,32 , a recent experimental study has demonstrated that OC can become glycated through a post-translational modification at the N-terminus, which could have important implications on energy dissipation potential of this NCP. While this study suggests that this glycation was unlikely to interfere with OC's interaction with HAp, it is notable that these findings were based on a fragmented OC protein in which the fragmentation occurred between 19 and 20 residues.…”
Section: Mahdi Tavakol and Ted J Vaughan *mentioning
confidence: 99%
“…Output signals from the suprachiasmatic nuclei (SCN) are believed to transmit standard circadian time to peripheral tissues through humoral routes and the sympathetic nervous system [ 23 , 24 ]. Some papers have indicated that the sympathetic nervous system mediates the expression of core clock genes and regulates bone remodeling [ 25 ].…”
Section: Discussionmentioning
confidence: 99%